Amino-terminal propeptide of type III procollagen is associated with restrictive mitral filling pattern in patients with dilated cardiomyopathy: a possible link between diastolic dysfunction and prognosis. Issue 6 (14th May 2004) - Rossi, A; Cicoira, M; Golia, G; Zanolla, L; Franceschini, L; Marino, P; Graziani, M; Zardini, P
Abstract : Objective: To analyse the relation between restrictive mitral pattern, amino-terminal propeptide of type III procollagen (PIIINP), and prognosis in patients with dilated cardiomyopathy. Design: Prospective cohort study of 106 patients with dilated cardiomyopathy. Setting: Tertiary care centre. Main outcome measures: PIIINP concentration, echocardiographic variables, oxygen consumption, hospitalisation for heart failure, and cardiac mortality were evaluated in patients grouped by the presence of non-restrictive (group 1), reversible (group 2), and irreversible restrictive mitral pattern (group 3). Results: Groups differed regarding left ventricular ejection fraction (group 1, mean (SD) 36 (6)%, group 2, 29 (8)%, group 3, 25 (6)%; p = 0.0001), left atrial ejection fraction (group 1, 0.47 (0.1)%, group 2, 0.43 (0.2)%, group 3, 0.26 (0.1)%; p < 0.0001), and PIIINP (p = 0.001). Multivariate analysis showed that PIIINP was related to mitral pattern (odds ratio 0.8, 95% confidence interval 0.23 to 1.4, p = 0.006) independently of left atrial and ventricular ejection fractions. After 21 months, survival was 88% and 34% (p = 0.0001) in patients with non-restrictive and irreversible restrictive mitral patterns, respectively. Conclusion: In patients with dilated cardiomyopathy, restrictive mitral pattern is associated with higher PIIINP and worse prognosis.